A review of moving-bed biofilm reactor technology for palm oil mill effluent treatment. (10th January 2018) - Abu Bakar, Siti Nur Hatika; Abu Hasan, Hassimi; Mohammad, Abdul Wahab; Sheikh Abdullah, Siti Rozaimah; Haan, Teow Yeit; Ngteni, Rahmat; Yusof, Khairul Muis Mohamed
Abstract: This review focuses on the advantages and challenges of using moving-bed biofilm reactor technology as an effective aerobic polishing treatment unit for palm oil mill effluent with the aim of achieving the goal of 'zero discharge'. The main idea of this paper is to discuss the palm oil industry as a whole, paying particular attention to (1) current treatment techniques, (2) state-of-the-art moving-bed biofilm reactor technology for palm oil mill effluent treatment and (3) the operating design of moving-bed biofilm reactor technology co-assisted by biofilms, including the flow configuration, aeration mode and types, and characteristics of the media. In addition, the integration of moving-bed biofilm reactors with other treatment unit processes, such as membranes and coagulation, is also discussed. Based on this review, moving-bed biofilm reactors are considered to be an impactful polishing treatment technology in the treatment of palm oil mill effluent. Graphical abstract: Highlights: The current palm oil effluent treatment technology was discussed. The adverse effect of palm oil mill effluent to the environment was explained. The moving-bed biofilm reactors for palm oil mill effluent treatment were discussed. The treatment of palm oil mill effluent aimed to achieve 'zero discharge purpose'.